Optimizing Patient Access to Orphan Medicinal Products: Lessons from Central and Eastern Europe - Kluszczynski, Tomasz; Nemeth, Bertalan; Władysiuk, Magdalena; Czech, Marcin; Kamusheva, Maria; Fotin, Nicolae; Rose, Sandra; Doležal, Tomáš; Hren, Rok (Journal of market access & health policy, 2025)
This study examines patient access to orphan medicinal products (OMPs) in Central and Eastern Europe (CEE) over the past five years, focusing on seven countries: Bulgaria, Czechia, Hungary, Poland, Romania, Slovakia, and Slovenia. While these jurisdictions have undergone rapid healthcare transformations, significant disparities in OMP access persist compared to Western Europe. This study aimed to address this gap by identifying barriers and enablers to optimize patient access to OMPs in a sustainable and equitable manner. A mixed-methodology approach was utilized, combining systematic literature reviews, in-depth interviews, and advisory board insights. Perspectives were gathered from a wide range of stakeholders, including policymakers, payers, academia, industry associations, and patient advocacy groups. Additionally, the study incorporated data from CEE-specific initiatives to triangulate findings and evaluate barriers, enablers, and best practices in OMP access. The analysis identified sub-optimal OMP access across most CEE countries, marked by prolonged delays and lower reimbursement rates compared to Western Europe, with Slovenia and Czechia as notable exceptions. Key barriers include limited awareness, inadequate health technology assessment (HTA) frameworks, insufficient financing mechanisms, underutilization of novel access schemes, and fragmented patient engagement. Conversely, enablers include the presence of rare disease policies, OMP-specific HTA frameworks, and patient-inclusive decision-making processes.
Keywords: orphan medicinal products; healthcare disparities; Central and Eastern Europe; regional collaboration; rare diseases; patient access; health technology assessment